Applications of the RTgill‐W1 Cell Line for Acute Whole‐Effluent Toxicity Testing: In Vitro–In Vivo Correlation and Optimization of Exposure Conditions. (27th January 2021) - Scott, Justin; Belden, Jason B.; Minghetti, Matteo
Abstract: The cell line RTgill‐W1 was evaluated as an in vitro alternative model for acute fish whole‐effluent toxicity (WET) testing. We determined the 50% effective concentration (EC50) that reduces the viability of RTgill‐W1 cells for selected toxicants commonly found in effluent samples and correlated those values with the respective 50% lethal concentration (LC50) of freshwater (fathead minnow, Pimephales promelas ) and marine (sheepshead minnow, Cyprinodon variegatus ) fish species obtained from the literature. Excluding low water‐soluble organics and the volatile sodium hypochlorite, significant correlations were measured for metal, metalloids, ammonia, and higher water‐soluble organics between in vitro EC50 values and in vivo LC50 values for both species. Typically, toxicity studies with RTgill‐W1 cells are conducted by adding salts to the exposure medium, which may affect the bioavailability of toxicants. Osmotic tolerance of RTgill‐W1 cells was found between 150 and 450 mOsm/kg, which were set as the hypoosmotic and hyperosmotic limits. A subset of the toxicants were then reexamined in hypoosmotic and hyperosmotic media. Copper toxicity decreased in hyperosmotic medium, and nickel toxicity increased in hypoosmotic and hyperosmotic media. Linear alkylbenzene sulfonate toxicity was not affected by the medium osmolality. Overall, RTgill‐W1 cells have shown potential for applications in measuring metal, metalloids, ammonia, and water‐soluble organic chemicals in acute WET tests, as well as complementing current toxicity identification and reduction evaluation strategies. In the present study, RTgill‐W1 cells have been established as a valid animal alternative for WET testing, and we show that through manipulation of medium osmotic ranges, sensitivity to nickel was enhanced. Environ Toxicol Chem 2021;40:1050–1061. © 2020 SETAC Abstract : Utilizing RTgill‐W1 cells as an in vitro animal alternative for acute whole‐effluent toxicity testing. EC50 = median effective concentration; LAS = linear alkylbenzene sulfonate; LC50 = median lethal concentration; QAC = quaternary ammonium compound (74.5% benzyldimethyldodecylammonium chloride, 22.3% benzyldimethyltetradecylammonium chloride).